Keratoconus Progression in Patients With Allergy and Elevated Surface Matrix Metalloproteinase 9 Point-of-Care Test. (November 2018) - Mazzotta, Cosimo; Traversi, Claudio; Mellace, Pierfrancesco; Bagaglia, Simone A.; Zuccarini, Silvio; Mencucci, Rita; Jacob, Soosan
Abstract : Purpose: To assess keratoconus (KC) progression in patients with allergies who also tested positive to surface matrix metalloproteinase 9 (MMP-9) point-of-care test. Methods: Prospective comparative study including 100 stage I–II keratoconic patients, mean age 16.7±4.6 years. All patients underwent an anamnestic questionnaire for concomitant allergic diseases and were screened with the MMP-9 point-of-care test. Patients were divided into two groups: patients KC with allergies (KC AL) and patients KC without allergies (KC NAL). Severity of allergy was established by papillary subtarsal response grade and KC progression assessed by Scheimpflug corneal tomography, corrected distance visual acuity (CDVA) measurement in a 12-month follow-up. Results: The KC AL group included 52 patients and the KC NAL group 48. In the KC AL group, 42/52 of patients (81%) were positive to MMP-9 point-of-care test versus two positive patients in the KC NAL group (4%). The KC AL group data showed a statistically significant decrease of average CDVA, from 0.155±0.11 to 0.301±0.2 logarithm of the minimum angle of resolution ( P <0.005) at 12 months; Kmax value increased significantly, from 50.2 D±2.7 to 55.2 D±1.9 on average. The KC NAL group revealed a slight KC progression without statistically significant changes. Pearson correlation test showed a high correlation between Kmax worsening and severity of PSR in the KC AL group. Conclusions: The study demonstrated a statistically significant progression of KC in patients with concomitant allergies, positive to MMP-9 point-of-care test versus negative. A high correlation between severity of allergy and KC progression was documented.